Azithromycin and the Treatment of Lymphocytic Airway Inflammation After Lung Transplantation. Issue 12 (13th November 2014) - Vos, R.; Verleden, S. E.; Ruttens, D.; Vandermeulen, E.; Bellon, H.; Neyrinck, A.; Van Raemdonck, D. E.; Yserbyt, J.; Dupont, L. J.; Verbeken, E. K.; Moelants, E.; Mortier, A.; et al.
<x xml:space="preserve">Abstract</x> Lymphocytic airway inflammation is a major risk factor for chronic lung allograft dysfunction, for which there is no established treatment. We investigated whether azithromycin could control lymphocytic airway inflammation and improve allograft function. Fifteen lung transplant recipients demonstrating acute allograft dysfunction due to isolated lymphocytic airway inflammation were prospectively treated with azithromycin for at least 6 months (NCT01109160). Spirometry (FVC, FEV1, FEF25–75, Tiffeneau index) and FeNO were assessed before and up to 12 months after initiation of azithromycin. Radiologic features, local inflammation assessed on airway biopsy (rejection score, IL‐17+ cells/mm2 lamina propria) and broncho‐alveolar lavage fluid (total and differential cell counts, chemokine and cytokine levels); as well as systemic C‐reactive protein levels were compared between baseline and after 3 months of treatment. Airflow improved and FeNO decreased to baseline levels after 1 month of azithromycin and were sustained thereafter. After 3 months of treatment, radiologic abnormalities, submucosal cellular inflammation, lavage protein levels of IL‐1β, IL‐8/CXCL‐8, IP‐10/CXCL‐10, RANTES/CCL5, MIP1‐α/CCL3, MIP‐1β/CCL4, Eotaxin, PDGF‐BB, total cell count, neutrophils and eosinophils, as well as plasma C‐reactive protein levels all significantly decreased compared to baseline (p < 0.05). Administration of azithromycin was associated with suppression of posttransplant lymphocytic airway inflammation and clinical improvement in lung allograft function.